COMPARISON OF TWO DIFFERENT SPINAL DOSES OF 0.75% BUPIVACAINE CAUSING MATERNAL HYPOTENSION IN ELECTIVE CAESAREAN SECTION - Saifullah Channa (Army Medical College Rawalpindi, 2019)
Objective: To compare the frequency of maternal hypotension between spinal doses of 7.5 mg and 15 mg of 0.75% hyperbaric bupivacaine in elective caesarean section.